Tea seed meal application promoted microbial community diversity in the soil of peach orchard - Sun, Ping; Shen, Jiansheng; Lin, Xianrui; Zong, Yu; Wang, Yi; Zhu, Jianxi; Chen, Chenfei; Wang, Yanqiao; Jia, Huijuan; Wang, Xinwei (Dryad, 2022)
Soil microbes are indispensable in agricultural production, and they
respond differently to different fertilization regimes. However, there is
limited understating of microbial composition and function responses to an
organic fertilizer tea seed meal (TSM) and conventional fertilizer. Here
we first reported the change rules and functions of soil microbial
community in peach orchard soil after application of compound fertilizer
plus urea (CFU) and different amounts (1.25, 2.50, 3.75 and 5.00 kg) of
TSM. Compared to CFU, the application of 1.25, 2.50 and 3.75 kg TSM
significantly decreased the Chao1 index of bacterial community in peach
orchard soil. The Shannon index of bacterial and fungal communities in
2.50 kg TSM treatment was significantly higher than that in CFU. Beta
diversity analysis of bacteria and fungi (based on Bray-Curtis matrix and
OTUs level) revealed significant structural differences among all five
experimental groups (ANOSIM, bacteria: R= 0.665, p = 0.001; fungi: R=
0.996, p = 0.001). The TSM treatments significantly decreased the relative
abundances of potentially unfriendly bacteria (Acidothermus, Acidicaldus,
Sphingomonas, Candidatus Koribacter and Candidatus Solibacter) and fungi
(Fusarium), and significantly increased the relative abundances of
potentially beneficial fungi (Trechispora, Sagenomella, Penicillium,
Acaulium caviariforme, Leucoagaricus and Chlorophyllum) compared with CFU.
These changes were more obvious when the application amount of TSM was
2.50 kg. This study provides insights into the potential of application of
TSM as an organic fertilizer in agricultural production.
Keywords: FOS: Agricultural sciences; internal transcribed spacer (ITS)